Analysis of Applying of Sustainability Business for Cooperative Reputation - Muhammad Nashar (Coopetition : Jurnal Ilmiah Manajemen, 2023)
The cooperative has been occurring poor performance, low competitiveness, lack of professionalism, unresponsiveness to changes in the business environment, inefficient management of the economy and business sector and the fragile banking system are fundamental weaknesses in cooperatives in Indonesia. The reputation of the Cooperative is a factor that Corporate Governance is one of the factors that can be analyzed as a lack of good relations between various stakeholders. The city of South Tangerang as a relatively new city has about 5 cooperatives that have been maintained by the Dinas Koperasi and have constraints such as reputation and cooperative governance. This research is qualitative research with a case study approach based on predetermined criteria. The results of this study are in the form of an overview of the cooperative management in South Tangerang and its recommendations.